A Constraint-Based Approach to Visual Speech for a Mexican-Spanish Talking Head. (24th February 2008) - Lazalde, Oscar Martinez; Maddock, Steve; Meredith, Michael
Abstract : A common approach to produce visual speech is to interpolate the parameters describing a sequence of mouth shapes, known as visemes, where a viseme corresponds to a phoneme in an utterance. The interpolation process must consider the issue of context-dependent shape, or coarticulation, in order to produce realistic-looking speech. We describe an approach to such pose-based interpolation that deals with coarticulation using a constraint-based technique. This is demonstrated using a Mexican-Spanish talking head, which can vary its speed of talking and produce coarticulation effects.